Solving Geometry Through Triadic Cycles on Harel’s Theory: A Systematic Case Study Procedure - Resy Nirawati (Proceeding of International Conference on Multidisciplinary Research, 2024)
Harel interprets mathematics as the relationship between mental acts, ways of thinking, and ways of understanding that are covered in the triadic cycle. This study aims to examine mental acts, thinking, and understanding in solving geometry problems. Data were obtained from 28 students using written test instruments on geometry materials. This research was analyzed qualitatively using a holistic type case study design with grounded theory data analysis techniques assisted by ATLAS.ti 9 software. Data is collected through tests, observations, documentation, and interviews. Data analysis includes data reduction, presentation, and conclusion drawing. Grounded theory analysis of mathematical procedures using ATLAS ti.9 software consists of the stages of open coding, axial coding, and selective coding found three theme and three categories including the theme of the mental act with the categories of interpreting, explaining, problem-solving. The theme of ways of thinking with multiple interpretations, ways of explaining, and strategic problem-solving. Then found the theme of ways of thinking with the categories of interpretation, explanation, and solution. Grounded theory analysis of systematic procedures produces a hypothetical conclusion. How students think in solving geometry problems affects how to understand new concepts correctly and precisely